Advancements in Cellular Automata Modeling for Corrosion Management and Predictive Maintenance - Juan C. Reinoso-Burrows; Marcelo Cortés-Carmona; Mauro Henriquez; Felipe M. Galleguillos Madrid (Chemical and Materials Sciences: Developments and Innovations Vol. 9, 2025)
Corrosion refers to the irreversible reaction between a material and its environment, which can result in the degradation of the material and its properties. It is a natural process that occurs when a metal is exposed to oxygen and moisture. It has a significant economic impact, representing approximately 3.4% of the global Gross Domestic Product (GDP). Cellular automata models have emerged as a valuable tool in corrosion management. The aim of the study is to this manuscript provides an overview of the application of cellular automata models in corrosion research, highlighting their benefits and contributions to understanding the complex nature of corrosion processes. Cellular automata models offer a computational approach to simulating corrosion behavior at the microscale, capturing the intricate interactions between electrochemical reactions, material properties, and environmental factors and generating a new vision of predictive maintenance. It reviews the key features of cellular automata, such as the grid-based representation of the material surface, the definition of state variables, and the rules governing cell-state transitions. The ability to model local interactions and emergent global behavior makes cellular automata particularly suitable for simulating corrosion processes. The study concluded that cellular automata models offer a powerful and versatile approach to studying corrosion processes, expanding models that can continue to enhance our understanding of corrosion and contribute to the development of effective corrosion prevention and control strategies. Their effective capture of the intricate dynamics of corrosion processes presents an opportunity to develop predictive models, corrosion-resistant materials, and real-time monitoring systems. Although challenges remain to be addressed, the prospects of utilizing Cellular Automata in corrosion management appear encouraging. Furthermore, the model’s ability to represent multiple types of physical phenomena makes it a powerful tool that can help researchers view the studied phenomena from a different perspective.